Вплив представників класичної філософії на педагогічні методи Алена - Мартьянова, Марія Євгеніївна; Martianova, M. Ye. (My University, 2019)
У статті розглянуто основні педагогічні погляди, які розділяє Ален (Еміль-Огюст Шартьє) з французьким філософом Ж.-Ж. Руссо та нідерландським філософом Б. Спінозою. Визначено основні паралелі в педагогічних концепцій французьких вчених, такі як ідея свободи мислення і судження та виховання працездатності під час навчання. З’ясовано, що при вивченні методів морального виховання, Ален звертався до робіт Б. Спінози. Виявлено, що обидва вчених виказували думку, що освіта базується на загальній цілі – пошуку істини людського буття. Встановлено, що процес пізнання допомагає впоратися з афектами та сприяє самодовдосконаленню. The article is devoted to the main pedagogical views of such scientists as Alain (Emile Auguste Chartier), J.- J.Russo and B.Spinoza. It was found out that Alain had analyzed the ideas of his colleagues in his works “History of my thoughts” and “Spinoza”. It was formed the main theses of Rousseau’s pedagogical concepts. One of them is contact with nature, an important component which helps to develop natural skills and gain experience. The principle of freedom is based on working competence. Working is also described as an educative method which helps to form positive moral qualities. The method of interview with a teacher, which aim is to develop communicative skills and found out interesting and necessary information, is presented. It is considered that the method of “natural consequences”, which includes the analysis of wrong actions, inculcates resolute qualities. The scientist criticized artificial illustrations, insisting on instructions by means of showing objects. The article determines the main parallels of pedagogical concepts of French philosophers (Alain and J.-J. Russo), such as: the idea of freedom of thought, and judgment and the education of efficiency during studing. It was found out that during studying the methods of moral education, Alain referred to B. Spinoza’s works. The main theorems from Spinoza’s “Ethica Ordine Geometrico Demonstrata” were described. They are natural beginning in all spheres of human activity, active attitude to life which contains will power and energy and hard-working nature. It was stressed that the main target of education is not only the preparing for the adulthood, but also student’s self-improvement. The position of the struggle with passions and the concentration on the idea of moral and spiritual growth is considered to be the main way of self-improvement. The Spinoza’s and Russo’s influence on Alain’s pedagogical methods is proved.
The influence of representatives of classical philosophy on Alain’s pedagogical methods
Keywords: принцип природи; працездатність; метод “інтерв’ю”; мораль; активний підхід; a principle of nature; working capacity; a method of “interview”; morality; an active approach